Impact of the number of cryopreserved CD34+ cells in the infused blood grafts on hematologic recovery and survival in myeloma patients after autologous stem cell transplantation: Experience from the GOA study. Issue 1 (14th October 2022) - Partanen, Anu; Turunen, Antti; Silvennoinen, Raija; Valtola, Jaakko; Pyörälä, Marja; Siitonen, Timo; Sikiö, Anu; Putkonen, Mervi; Sankelo, Marja; Penttilä, Karri; Kuittinen, Taru; Mäntymaa, Pentti; et al.
Abstract: Background: Prospective data on the impact of CD34 + cell loss during cryopreservation and the amount of cryopreserved CD34 + cells infused after high‐dose therapy on hematologic recovery and post‐transplant outcome in multiple myeloma (MM) are scarce. Patients and methods: This post‐hoc study aimed to investigate factors associating with CD34 + cell loss during cryopreservation and the effects of the infusion of a very low number (<1.0 × 10 6 /kg, group A), low number (1–1.9 × 10 6 /kg, group B), and optimal number (≥2 × 10 6 /kg, group C) of thawed viable CD34 + cells on hematologic recovery, progression free survival, and overall survival after autologous stem cell transplantation among 127 patients with MM. Results: In group C, pegfilgrastim use ( P  = 0.001), plerixafor use ( P  = 0.039), and older age ≥ 60 years ( P  = 0.026) were associated with less loss of CD34 + cells during cryopreservation. Better mobilization efficacy correlated with greater CD34 + cell loss in group B ( P  = 0.013 and P  = 0.001) and in group C ( P  < 0.001 and P  < 0.001). Early platelet engraftment was slowest in group A (20 d vs 12 d in group B vs 11 d in group C, P  = 0.003). The infused viable CD34 + cell count <1.0 × 10 6 /kg seemed not to have influence on PFS ( P  = 0.322) or OS ( P  = 0.378) in MM patients. Conclusions: Cryopreservation impacts significantly on the CD34 + cell loss. A very low number of graft viable CD34 + cells did not affect PFS or OS.